Teaching theology in the Fourth Industrial Revolution - Oliver, Willem H. (HTS teologiese studies, 2020)
Post-school education (PSE) in South Africa mostly takes place within an industrial-age factory environment as has been done for the past 50 years or longer. This is the case despite the fact that the world is on the brink of, or already part of, the Fourth Industrial Revolution (4IR), called by some an ‘emerging new world order’. Educating students today like we did it half a century ago has now become education to a ‘quickly vanishing world’. Although one may argue that the content of Theology will not be much affected by the 4IR, it is proposed that the way in which that content is communicated and educated should change drastically. Doing this will prepare our students to become relevant preachers or theologians in the current (post-)postmodern society. The proposed model in this article is called an outside-in model – contrasted to the current inside-out model of education – in which our students should be taught to develop a sense of deep learning, to effectively learn and work in and with groups, to use their mobile devices (cell phones and tablets) and social media within the environment of education and to discuss new ways of gathering God’s people.The question that each educator should ask themselves nowadays is: Am I really preparing my students for the future that they are facing?Contribution: A new way of teaching Theology in the 4IR is imperative for our students. This article suggests how it could be done. Although this entails willpower and persuading the mostly ‘old’ lecturers in Theology to engage with real technology, it is all about the student, because many of these students will become the lecturers of tomorrow. Our faculties or departments of Theology are therefore urged to fit themselves into the new mould and to train our future theologians in a 4IR way.